Role of semen analysis in the diagnosis of infertility at a tertiary care centre in Western India: a prospective study - Jain, Atul; Ambrish, Puja Iyengar; MB, Hoogar; Dhar, Reeta; Wani, Ajay; Agrwal, Shonit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of infertility in the general population is 15%-20%. Of this, the male factor is responsible for 20%-40%. In Indian couples seeking treatment, the male factor is the cause in approximately 23%. Semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Careful evaluation of the ejaculate parameters may suggest the possible causes of infertility and their identification could help to institute appropriate therapy, if available. Methods: Semen samples were analyzed by manual method. An analysis for volume, viscosity, sperm concentration, motility, and morphology, according to WHO guidelines on semen analysis was done. Results: This study, done at a tertiary care center at Western India, at M.G.M hospital has demonstrated that abnormal semen quality is a major factor contributing to infertility in couples.28% males had volume <2 ml, 70% had sperm count <20 million/ml and 72% had sperms with abnormal morphology. Conclusions: Semen analysis remains a significant contribution in the overall diagnosis of infertility in our environment and semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Males contribute towards infertility in couples significantly and further study and assessment is required to accurately predict the importance of this.